Analisis Pengendalian Persediaan Bahan Baku Tandan Buah Segar (TBS) dalam Menunjang Efektivitas Pengelolaan Persediaan Pada Pusat Penelitian Kelapa Sawit (PPKS) Medan - Aprilla Wardhahany Siregar; Nur Fadhilah Ahmad Hasibuan (Akuntansi, 2024)
This research aims to determine the control of raw material supplies of Fresh Fruit Bunches (FFB) in supporting the effectiveness of raw material management at PPKS Medan. The data analysis method used is qualitative analysis with a case study approach. This type of research is descriptive qualitative research. The data sources used in the research used primary and secondary data sources. The data techniques used are documentation review techniques, observation and interview techniques. Incompatibility in the application of the FIFO inventory assessment method at PPKS Medan in the field, inventory discrepancies that are often identified. Discrepancies that can occur are differences between physical products and inventory reports. Reasons for inventory discrepancies are warehouse management, proof of receipt, or proof of unrecorded costs. There are notes on the recording note that were not recorded at the time of delivery of goods, missing warehouse notes as proof of receipt or release of goods, incorrect exit or entry of goods, for example slips if there is no warehousing request. This research uses physical and perpetual recording methods and uses the FIFO inventory recording method. Based on the results of the analysis of Standard Operating Procedures (SOP) for inventory, PPKS Medan has not implemented the elements of raw material inventory management effectively as evidenced by the FIFO inventory assessment method not being implemented correctly, and raw material inventory control at PPKS Medan is still not optimal, as shown by the It often happens that orders for inventory are double delivered, resulting in a buildup in the warehouse. Thus, the effectiveness of management of raw material supplies can be concluded that control of the management of raw material supplies of Fresh Fruit Bunches (TBS)) at PPKS Medan has not been effective as a whole.